Controllable preparation of crystalline red phosphorus and its photocatalytic properties. Issue 45 (15th November 2021) - Zhang, Shuai; Ma, Shufang; Hao, Xiaodong; Wang, Yunting; Cao, Ben; Han, Bin; Zhang, Hao; Kong, Xingang; Xu, Bingshe
Abstract : An element-assisted chemical vapor transport reaction was used not only to synthesize single-phase crystal red phosphorus [P12(4)]P2[micron belts, but also single-phase crystal Hittorf's phosphorus micron rods extending along the [001] direction. Abstract : Single-element phosphorus has received extensive attention in recent years because of its remarkable photocatalytic properties. In the present experiment, amorphous red phosphorus was controllably transformed into [P12(4)]P2[and Hittorf's phosphorus structures by performing bismuth catalysis. The temperature-controllable chemical vapor transport reaction realized the conversion of more than 90% of amorphous red phosphorus to single-phase crystalline red phosphorus. Under very mild ultrasonic treatment, the high-quality [P12(4)]P2[microbelts and Hittorf's phosphorus microrods were stripped into a few layers of nanobelts and sheet-like structures, respectively. As non-metallic catalysts, their rapid photocatalytic degradations of pollutants (methyl orange) and high hydrogen evolution rates revealed the rapid charge transfer and application potential of the crystalline red phosphorus catalyst. The results of this work could provide new ideas for the development of phosphorus-based crystalline photocatalytic systems.